Smart Traffic Light based on IoT and mBaaS using High Priority Vehicles Method - Muhammad Izzuddin Mahali; Eko Marpanaji; Satriyo Dewanto; Bekti Wulandari; Umi Rochayati; Nur Hasanah (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
An increase of the number of vehicles which is not followed by the number of roads can lead to the increase of congestion, especially in big cities. Regulation of law no 22 Year 2009 explains that there are seven types of vehicles prioritized on the road. This research aims to build a Smart Traffic Light as a solution with the goal of making the prioritized vehicle journey smooth when crossing the road with Smart Traffic Light. The proposed system is "Smart Traffic Light on IoT and mBaaS (Mobile Backend As a Service) using High Priority Vehicles Method". The Smart Traffic Light has three important parts, including: (1) Smart Traffic Application; (2) Smart Traffic Controller; and (3) mBaaS. Prioritized vehicle drivers cross the road using the Smart Traffic Application when they are in an emergency situation. Smart Traffic Application and Smart Traffic Controller communicate using mBaaS. Smart Traffic Application has a vehicle track search facility as well as identification of traffic light location. A few meters before crossing, Smart Traffic Application will send the location to mBaaS and continue to be read by Smart Traffic Controller using internet. If it meets the criteria of High Priority Vehicle, then Traffic Light will be changed to green in the same path. The results show that when testing the data rate from Smart Traffic Application to Smart Traffic Controller, it takes no later than 8.15 seconds and 1.2 seconds (the fastest) with the average data transmission time of 3.39 seconds. Smart Traffic Light is able to identify the direction of the vehicle before passing through the Smart Traffic Application.